(untitled) (Teología, 2019)
This is part I of a two part contribution dealing with relationship between an evangelizing spirituality “going out” (Pope Francis’ concept expressed in Evangelii gaudium) and this Pope’s visit to Chile, January 15-18, 2018. What can this spirituality offer in the face of the institutional crisis of the Catholic Church caused by sexual abuse by priests or religious members in this country? And what contribution can Francis’ visit itself make to deepen this evangelizing spirituality “going out”? How to assess the meeting between Francis and God’s Pilgrim People in Chile? In order to answer these questions, first a partial view of spirituality will be offered for the sake of an evangelization focusing on “going out”. Second, a dialog will be attempted between Francis’ teaching and the event of the Pope’ visit to Chile, with the help of a “three-fold hermeneutics” of theology, the teaching of the Church, and written reports by the press. By theologically interpreting Francis’ visit to Chile, we hope to inspire new ways for the Church to come out of its present-day crisis.